ENHANCING METHANE OXIDATION IN LANDFILL COVER USING BREWERY SPENT GRAIN AS BIOCOVER - G., Siva Shangari,; P., Agamuthu (Malaysian Journal of Science, 2012)
Landfill gas (LFG) is a potent greenhouse gas (GHG) generated by anaerobic degradation of decomposable municipal solid wastes (MSW). LFG contains (50-60%) of methane (CH4) and (40â€“50%) carbon dioxide (CO2). If a landfill is neither aerated nor equipped with gas capture systems, the LFG emissions, mainly CH4, in the cover soil is best reduced by using a biocover. Biocovers normally act as a biofilter to reduce emissions by improving the biological oxidation of CH4 to CO2. In this study, the optimal ratio for a biocover using mixture of brewery spent grain (BSG) and compost made out of grass and cow manure is determined. Thereafter, column experiments were carried out to investigate the best height level of the biocover. Batch incubation experiments were conducted for screening the best ratio of BSG to compost. A mixing ratio from 10% to 100% BSG to compost with 10% increment was tested. The best ratio of BSG to compost was 7:3. This ratio was later tested with different parameters such as pH, moisture content and temperature. Overall, the optimum biocover performance was at pH 6, moisture content of 66% (v/v) and temperature of 40Â°C. The column experiments showed that 100% CH4 oxidation occurred fastest at the height of 50cm. (Keywords: Greenhouse gas, methane oxidation, biocover, brewery spent grain, compost)